Gender differences in quality of dying and death among older adults: a cross-sectional study in China - Xiaohong Feng; Shumei Liang; Xiujun Dai; Jinlin Du; Zheng Yang (Frontiers in Public Health)
BackgroundThe aging of China is deepening year by year, and improving the quality of dying and death (QODD) is increasingly becoming an urgent and realistic need. This study explores the gender differences in the quality of dying and death and its influencing factors among Chinese older adults, aiming to provide assistance to the relevant authorities in formulating end-of-life care policies for the older adults, and to adapt to the needs of an aging society.MethodsBased on the data of the Chinese Longitudinal Health Longevity Survey (CLHLS) during 2008–2018, a total of 7,341 respondents were included. Chi-square test and logistic regression analysis were used to analyze the quality of dying and death among Chinese older adults and its influencing factors. In addition, A Fairlie decomposition analysis (FDA) was conducted to ascertain the degree of influence exerted by various contributing factors.ResultsThe proportion of high QODD among female older adults (63.80%) was significantly higher than male older adults (56.00%), which was statistically significant. Logistic regression showed that age, residence, home facilities score, place of death, medical costs, got timely treatment, number of chronic diseases and unconsciousness were the factors influencing QODD among male older adults. Meanwhile, residence, marital status, home facilities score, place of death, got timely treatment, bedridden, suffered from serious illness, unconsciousness and drinking were the factors influencing QODD among female older adults. FDA showed that 47.89% of the differences in QODD were caused by the observed variables, while 52.11% of the differences were caused by gender differences and unmeasured variables.ConclusionChinese men have a poorer QODD compared to women. The main factors contributing to this difference were age, the number of chronic diseases, suffered from serious illness, unconsciousness, place of death, residence and home facilities scores. To ensure successful aging, the relevant departments should focus on these factors and work toward reducing the gender differences in QODD.